Cylindrical Costal Osteochondral Autograft for Reconstruction of Large Defects of the Capitellum Due to Osteochondritis Dissecans - Shimada, Kozo (Journal of Bone and Joint Surgery, Inc., 2012)
BACKGROUND: There is a need to clarify the usefulness of and problems associated with cylindrical costal osteochondral autograft for reconstruction of large defects of the capitellum due to osteochondritis dissecans. METHODS: Twenty-six patients with advanced osteochondritis dissecans of the humeral capitellum were treated with use of cylindrical costal osteochondral autograft. All were males with elbow pain and full-thickness articular cartilage lesions of ≥15 mm in diameter. Clinical, radiographic, and magnetic resonance imaging outcomes were evaluated at a mean follow-up of thirty-six months (range, twenty-four to fifty-one months). RESULTS: All patients had rapid functional improvement after treatment with costal osteochondral autograft and returned to their former activities, including sports. Five patients needed additional minor surgical procedures, including screw removal, loose body removal, and shaving of protruded articular cartilage. Mean elbow function, assessed with use of the clinical rating system of Timmerman and Andrews, was 111 points preoperatively and improved to 180 points at the time of follow-up and to 190 points after the five patients underwent the additional operations. Mean elbow motion was 126° of flexion with 16° of extension loss preoperatively and improved to 133° of flexion with 3° of extension loss at the time of follow-up. Osseous union of the graft on radiographs was obtained within three months in all patients. Revascularization of the graft depicted on T1-weighted magnetic resonance imaging and congruity of the reconstructed articular surface depicted on T2-weighted or short tau inversion recovery imaging were assessed at twelve and twenty-four months postoperatively. Functional recovery was good, and all patients were satisfied with the final outcomes. CONCLUSIONS: Cylindrical costal osteochondral autograft was useful for the treatment of advanced osteochondritis dissecans of the humeral capitellum. Functional recovery was rapid after surgery. Additional operations were performed for five of the twenty-six patients, whereas the remaining patients showed essentially full recovery within a year. All patients were satisfied with the results at the time of short-term follow-up. LEVEL OF EVIDENCE: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.